The Influence of Financial Literacy, Financial Behavior, and Emotional Intelligence on Investment Decisions in the Capital Market for Generation Z in the City of Surabaya - Adellia Audrey Lovelyzia; Irantha Hendrika Kenang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to test and analyze the influence of financial literacy, financial behavior and emotional intelligence on investment decisions for generation Z in the city of Surabaya. This research uses a quantitative research approach with multiple linear regression analysis methods with a total of 190 samples who are capital market investors in the city of Surabaya with a generation Z background. The results of the research show that: (1) Financial literacy negatively and significantly influences capital market investment decisions in generation Z in the city of Surabaya; (2) Financial behavior positively and significantly influences capital market investment decisions among generation Z in the city of Surabaya; (3) Emotional intelligence negatively and significantly influences capital market investment decisions in generation Z in the city of Surabaya.